Cutout animation - Aiers, Bill; Wahlquist, Nancy; Curtis, Lance; Taylor, Russell (North Ryde, NSW. : Australian Film Television & Radio School, 1984)
An easy-to-follow explanation of the techniques and tricks of cutout animation
Copy available in DVD format
Editor, Bill Aiers
Voices: Lance Curtis, Russell Taylor
Keywords: Animation (Cinematography).